Meningkatkan Kecerdasan Naturalis Anak melalui Kegiatan Meronce Menggunakan Bahan Alam Pada Anak Usia 5-6 Tahun - Fitriah Hayati; Agustina Agustina (IAIN TERNATE, 2022)
Naturalist intelligence is intelligence in understanding nature, which includes the ability to identify and classify differences and similarities in characteristics between species, both flora and fauna. Children's naturalist intelligence at the age of 5-6 years appears in the form of having started to have a sense of sensitivity to the surrounding environment, they already have an interest in nature. However, based on observations of group A children at Bungong Nanggroe Kindergarten, it shows that the naturalist intelligence of children is still very low. This can be seen from the children's lack of interest in nature, plants and animals. The purpose of this study was to improve children's naturalist intelligence through activities using natural materials media for children aged 5-6 years at Bungong Nanggroe Kindergarten, Padang Tiji sub-district. The type of research used is classroom action research (CAR), with 15 children as the subject. The instrument used was an observation sheet and the data were analyzed using the percentage formula. The results of the first cycle of research indicate that the naturalist intelligence of children still needs improvement with the following data: 6 children have not developed (BB), 6 children are at the stage of starting to develop (MB), 2 children are at the stage of developing as expected (BSH) and 1 child at very well developed stage. The results of the second cycle of research showed an increase with the following data: 3 children were in the stage of starting to develop (MB), 6 children at the stage of developing as expected (BSH) and 6 children at the stage of developing very well (BSB). Thus it can be concluded that meronce activities using natural materials can increase naturalist intelligence in children aged 5-6 years.